The Role And Challenges Of English Teacher Professionalism In Improving The Quality Of Learning In The Classroom - Nadynne, Nadynne Athaya Harland; Jamaliyah Hasan Lubis; Aaala Yaseen Hassan (PEBSAS: Jurnal Pendidikan Bahasa dan Sastra, 2024)
Teacher professionalism has a central role in improving the quality of learning in the classroom. This article explores key aspects of teacher professionalism, including academic competence, pedagogical skills, ethical attitudes, and adaptability to current developments. The discussion regarding the positive impact on student development becomes the focus, providing an in-depth understanding of the importance of the role of teachers as the main pillar in producing a quality generation. In conclusion, increasing teacher professionalism is a strategic key in improving the quality of education. The professionalism of a teacher is the answer to all the challenges that exist in the world of education, especially in the classroom. The urgency in increasing professionalism is one of the efforts to face future challenges, therefore a teacher will continue to be required to be professional to meet existing challenges.